Response of Wet Seeded Rice Varieties to Sowing Dates - Shah, Mishri L; Bhurer, Kailash P (Nepal Agriculture Research Journal, 2010)
The experiment was conducted at Regional Agriculture Research Station, Parwanipur in two consecutive years to find out the suitable rice varieties for wet seeding conditions in relation to sowing dates. Yield components like tillers number/m2, number of filled grains/panicle and 1000-grain weight were found in the decreasing trend from the seeding of 15 of June onward. The percent decrease in the grain yield was 14.1, 31.8 and 50.6 in 1998/99 where as 4.8, 7.9 and 49.6 in 1999/00 on June 29 to July 14 seeding dates respectively as compared to 15 June seeding date. Radha 4 in the first and Chaite 2 in the second year recorded the highest grain yield of 3757 and 4197 kg/ha respectively. Interaction effect of the sowing dates and varieties was highly significant. Radha 4 produced the highest grain yield of 5039 kg/ha in 1998/99 where as Radha 4 and Chaite 6 were found at par in 1999/2000 seeded on 15 June. Radha 4 was the best variety for wet seeded conditions when seeded on 15 June. Chaite 2 had been observed good yielder in all seeding dates among the tested varieties. Key words: Grain yield; seeding dates; wet seeding rice DOI: 10.3126/narj.v6i0.3342 Nepal Agriculture Research Journal Vol.6 2005 pp.35-38